SOCIAL CAPITAL MOBILIZATION STRATEGY TO SUSTAIN COMMUNITY ENTREPRENEURSHIP IN URBAN NEIGHBORHOOD - Prihadi Nugroho (Diponegoro University, 2015)
Entrepreneurs in cities are prone to direct market change and urban growth in a country. Those who do not possess strong business network and strategic alliance are likely out of the game immediately. Building community entrepreneurship thus becomes critical to provide collective business network and learning, particularly for smaller entrepreneurs and new entrants, through the mobilization of social capital. This paper aims to examine how urban community institutionalizes the embedded stock of social capital in the neighborhood to cultivate sound entrepreneurial ambience parallel with the individual pursuit of profit maximization. The multiple strategies of incorporating traditional and informal inherited values into the contemporary dynamics of market and urban growth are quite successful to sustain the continuation of home-based industry in the neighborhood. The case study approach was undertaken to observe the re-emergence of local batik industry in Kampung Laweyan of Surakarta Municipality, Indonesia. The result demonstrates that social cohesion safeguarding is the key to encourage collective entrepreneurial skills development in the community albeit it does not affect much the building of stronger inter-firm cooperation.